Al-munawwar via mooc : a platform for learning arabic language communication (level 1- beginner) - Ahmad Zaki Amiruddin; Wan Ab Aziz Wan Daud; Ahmad Abdul Rahman; Ahmed Thalal Hassan; Nor Abdul Rahman; Amanee Abdul Hai (2018)
Massive Open Online Course (MOOC) is an online-based course offered worldwide where any person can freely enroll it. MOOCs Malaysia has become the Ministry Prioritization Agenda under Leap 9: Globalized Online Learning under Malaysia's Education Development Plan 20152025. In line with that, UMK is bringing this idea as another tool in its educational system to improve the effectiveness of teaching and learning process. Online learning approach has the power to attract the involvement of current generations in learning activities as student and technology is a constant companion. Consequently, we design an online course known as MOOC Al – Munawwar through the website openlearning.com based on the ADDIE instructional design model. The online course was designed based on students’ needs, opinions, and suggestions, which were evaluated by the participants involved in this study, selected among students who are studying the Arabic language Communication level 1. Arabic online Course (Level 1) contains six (6) main chapters divided into 14 lessons for this MOOC offer. Each lesson focuses on the application of four language skills ie; written skills, listening skills, reading skills and basic speaking skills for beginners. The lessons presented are very simple, easy and suitable for beginner students who have no basic grammar in Arabic. Hence, the main focus of the course is the introduction of the Arabic language itself as well as the basics of Arabic that are easy to understand by beginner students. Keywords: MOOC, E-Learning,